2015
DOI: 10.18632/oncotarget.5590
|View full text |Cite
|
Sign up to set email alerts
|

Golgi protein 73 activation of MMP-13 promotes hepatocellular carcinoma cell invasion

Abstract: Golgi Protein 73 (GP73) is a serum biomarker for hepatocellular carcinoma (HCC), however its role in HCC is not clear. We report that GP73 promotes cell invasion, the hallmark of malignancy, through the upregulation of matrix metalloproteinase-13 (MMP-13). GP73 enhances MMP-13 expression through cAMP responsive element binding protein (CREB)-mediated transcription activation. Levels of GP73 and MMP-13 are increased and positively correlated in human HCC tissues. Augmented MMP-13 potentiates HCC cell metastasis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 31 publications
(31 reference statements)
1
37
0
Order By: Relevance
“…However, the mechanism by which GP73 promotes tumor progression remains unclear. Recently, a study demonstrated that GP73 potentiated HCC cell invasion by upregulating matrix metalloproteinase-13 (29), supporting the role of GP73 in HCC as suggested by the present study. In summary, the present study demonstrated that sGP73 was not a diagnostic marker but rather a prognostic factor for HCC.…”
Section: Discussionsupporting
confidence: 90%
“…However, the mechanism by which GP73 promotes tumor progression remains unclear. Recently, a study demonstrated that GP73 potentiated HCC cell invasion by upregulating matrix metalloproteinase-13 (29), supporting the role of GP73 in HCC as suggested by the present study. In summary, the present study demonstrated that sGP73 was not a diagnostic marker but rather a prognostic factor for HCC.…”
Section: Discussionsupporting
confidence: 90%
“…Currently, the knowledge on the function of GOLM1 is limited. It was reported that GOLM1 acts as a key oncogene by promoting tumor cell invasion, migration, growth, and metastasis in hepatocellular carcinoma and oesophageal cancer . GOLM1 augments hepatocellular carcinoma invasion through activation of the CREB‐MMP‐13 signaling pathway .…”
Section: Introductionmentioning
confidence: 99%
“…Jin et al reported that GOLPH2 promotes HCC invasion by activation of matrix metalloproteinase-13 (MMP-13) [32]. MMP-13 has a documented role in melanoma.…”
Section: Discussionmentioning
confidence: 99%